リュツォ ホルムワン ト ソノ エンガン チイキ ノ コウクウ ジキ ソクリョウ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 田島, 稔; タジマ, ミノル; 柿沼, 清一; カキヌマ, セイイチ; 吉田, 光雄; ヨシダ, ミツオ; 増田, 実; マズダ, ミノル; 吉村, 愛一郎; ヨシムラ, アイイチロウ; TAZIMA, Minoru; KAKINUMA, Seiichi; et al. (国立極地研究所, 1972)
P(論文) Since 1967 the aeromagnetic survey in the vicinity of Lutzow-Holm Bay, Antarctica, has been carried out by JARE. The total magnetic field was observed by means of a proton precession magnetometer, whose sensing head was to wed by a cable of about 10m in length from an airplane or a helicopter. Observation was made at intervals of 6-9 seconds and the total intensity was recorded continuously on an analogue recorder. Flight height was about 300m for helicopter and 1000m for airplane. Flight courses spread radially from Syowa Station, the total flight distance amounting to 2410km. The observed value was reduced to the common epoch of January 1, 1970, using the magnetic records of Syowa Station. The isomagnetic chart of total force was compiled. In general aspect and tendency of the distribution is similar to that of the International Geomagnetic Reference Field 1965.0 published by IAGA Commission 2 Working Group 4, except some amounts of differences in absolute value. Local magnetic anomalies more than 300γ are found along the Soya Coast and Padda Island, especially anomalies recorded over the southern part of the coast are remarkable. departmental bulletin paper